2019
DOI: 10.1177/1747493019874729
|View full text |Cite
|
Sign up to set email alerts
|

Stroke in the Middle-East and North Africa: A 2-year prospective observational study of intravenous thrombolysis treatment in the region. Results from the SITS-MENA Registry

Abstract: Background and methods Intravenous thrombolysis for acute ischemic stroke in the Middle-East and North African (MENA) countries is still confined to the main urban and university hospitals. This was a prospective observational study to examine outcomes of intravenous thrombolysis-treated stroke patients in the MENA region compared to the non-MENA stroke cohort in the SITS International Registry. Results Of 32,160 patients with ischemic stroke registered using the SITS intravenous thrombolysis protocol between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
29
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 20 publications
5
29
1
Order By: Relevance
“…The same results are consistent with those found in a recent observational study showing that hypertension, diabetes, smoking were the main risk factors identified in MENA countries [50]. Concerning the risk factors of IS between young people, HBP and smoking remains the most reported factors.…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 92%
See 1 more Smart Citation
“…The same results are consistent with those found in a recent observational study showing that hypertension, diabetes, smoking were the main risk factors identified in MENA countries [50]. Concerning the risk factors of IS between young people, HBP and smoking remains the most reported factors.…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 92%
“…Moreover, the same findings are in accordance with the results reported in the Middle East between 1980 and 2015 reporting gender differences, and that 75% of studies reported a high sex ratio in patients with stroke [52]. This is also confirmed by a recent observational study based on the results of the SITS-MENA register, which showed a male predominance (72%) in MENA countries compared to non-MENA countries (53.6%) [50]. This result could be due to hormonal factors including estrogen which seems to have protective effects on both the vascular and cerebral systems [53].…”
Section: The Percentage Of Patients With Thrombolyzed Ischemic Strokesupporting
confidence: 91%
“…Stroke incidence and mortality have increased in the countries of the Middle East and North Africa over the past decade, and projections indicate that stroke-related deaths will approximately double by 2030 in the same region [3,4]. Despite the rapid evolution of the generalization of intravenous thrombolysis in recent years in the countries of the Middle East and North Africa [5], the average symptom onset to arrival at a stroke center or emergency department (onset-to-door time [ODT]) of patients with ischemic stroke in Morocco remains very long, possibly resulting from a lack of knowledge, particularly of the first warning signs of an ischemic stroke, according to a recent systematic review [6].…”
Section: Introductionmentioning
confidence: 99%
“…6 The use of IV thrombolysis and MT has gained momentum in Saudi Arabia, but the published literature on the patterns and outcomes of thrombolysis remains scant. Recently, results from the Safe Implementation of Treatment in Stroke )SITS(-Middle East and North African )MENA( registry for IV thrombolysis were published, 7 and a report from Dubai described the use and outcomes of thrombolysis in 176 patients. 8 A stroke unit was formally established in our tertiary care center in 2012, although thrombolysis treatment was already offered prior to that.…”
Section: Discussionmentioning
confidence: 99%
“…10 The mean DTN times reported in the study from Dubai was 64.1 minute 8 whereas that reported in the SITS-MENA registry was 54 minutes. 7 Endovascular thrombectomy has become the standard of care for patients with LVO-related strokes. 12 Multiple randomized controlled trials published in 2015 had established the efficacy of endovascular/mechanical thrombectomy in LVO with no significant increase in sICH.…”
Section: Discussionmentioning
confidence: 99%